Teaching Innovation in the Development of Professional Practices: Use of the Collaborative Blog - Carmen Corujo-Vélez; Raquel Barragán-Sánchez; Carlos Hervás-Gómez; Antonio Palacios-Rodríguez (MDPI AG, 2021)
The development of professional practices during the university stage is a fundamental factor for quality skills development. For many students, it is the first real experience in a professional context, so continuous monitoring by teachers is necessary. This article presents an innovative proposal to develop the follow-up of the professional practices of the degree in Primary Education, and two Masters' in Psychopedagogy and Special Educational Needs using a learning management system (LMS) (Blackboard). The experience was developed by a team of teachers from the departments of Didactics and Educational Organization and Research Methods and Educational Diagnosis of the University of Seville (Spain). The aspects to be studied are the development of communication, reflection, and collaborative learning processes during the internship period. After an explicit agreement, 24 students (10 from the course "Professional Practices I" in undergraduate students; and the others from the Master's) committed to periodically using the blog designed ad hoc for this experience. A content analysis of the speeches posted on the blog was carried out, examining the changes, the advantages, and the disadvantages that this model entailed. It allowed observing similarities and differences between both groups of students. As the main conclusion, there were some differences between the two groups of students, regarding the number, type, and contents of interventions; there were no differences in the assessment of the methodology, all the students thought that it was a very positive assessment of the experience for generating information exchange networks among colleagues and teachers. Finally, the relevance of constant monitoring of the academic tutor was highlighted.